Acute Appendicitis Plus in Uterus Foreign Body: Clinical Case - Villalobos Rodríguez, Alejandro Lenin; Padrón Arredondo, Guillermo; Gómez-Aguilar, Dalia Lucía; Campos-Sanchez, Mónica; Sarmiento-Haydar, Orlando (British Journal of Healthcare and Medical Research, 2023)
Introduction. Uterine perforation by an intrauterine device (IUD) is classified into primary and secondary, the first case occurs within the first month of its insertion and the second after this period. This migration may be due to spontaneous uterine contractions, bladder contractions, increased intestinal peristalsis, and movement of peritoneal fluid. Clinical case. A 28-year-old patient came to the emergency department with abdominal pain that had lasted 8 hours until admission, accompanied by anorexia and nausea. Physical examination, a painful abdomen in the right iliac fossa with a positive Mc Burney sign. Vital signs with a low-grade fever of 37oC, BP ​​80/50, rest normal. Laboratories: leukocytosis 14.1/103 uL, neutrophilia 89%, rest normal, pregnancy test negative. The patient admitted to the operating room, and an open appendectomy was performed, finding a perforated appendix at the appendicular base with a retroileocecal abscess, classifying it as grade IV appendicitis. It was incident; the finding of an IUD emerging from the uterus a segment of the copper T that involves the right Fallopian tube and the rest into the utero is reported. Discussion. Reversible and long-acting contraceptives are safe and effective in their application, they involve the risk of immediate, mediate, and late uterine perforation, so their incidence is 1-2 cases per 1000 insertions; in the first setting it may be due to inexperience of the doctor who applies it by applying excessive force at the time of application, and it will surely give alarm symptoms immediately depending on the site of the perforation. Conclusions. How can be seen in this report, appendicular surgeries led to the location of this translocate IUD that had perforated the uterus and was halfway to being completely expelled. This finding is rare, and two pathologies were successfully resolved in the same surgical time.